Scopoletin and Scoparone from Viola philippica Attenuate the Virulence of Pseudomonas aeruginosa by Inhibiting Quorum Sensing-Related Genes - Luo Y; Zhang S; Ou S; Shen C; Xiao Q; Chen W; Pu J; Zeng J; Zheng D; Huang B; Chen C (Infection and Drug Resistance)
Yanfen Luo,1,2,* Shebin Zhang,1,2,* Songbang Ou,3,* Cong Shen,1,2,* Qian Xiao,1,2 Weiying Chen,4 Jieying Pu,1,2 Jianming Zeng,1,2 Dexiang Zheng,1,2 Bin Huang,5 Cha Chen1,2 1The Second Clinical Medical College, Guangzhou University of Chinese Medicine, State Key Laboratory of Dampness Syndrome of Chinese Medicine, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, 510000, People’s Republic of China; 2State Key Laboratory of Traditional Chinese Medicine Syndrome/Clinical Laboratory, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, 510000, People’s Republic of China; 3Reproductive Center, Department of Obstetrics and Gynecology, Sun Yat-Sen Memorial Hospital, Sun Yat-Sen University, Guangzhou, 510000, People’s Republic of China; 4Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, 510000, People’s Republic of China; 5Department of Laboratory Medicine, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, 510000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Cha Chen, The Second Clinical Medical College, Guangzhou University of Chinese Medicine, State Key Laboratory of Traditional Chinese Medicine Syndrome, Guangdong Provincial Hospital of Chinese Medicine, Guangzhou, People’s Republic of China, Tel/Fax +86-02039318325, Email chencha@gzucm.edu.cn Bin Huang, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, People’s Republic of China, Tel/Fax +86-02028823350, Email huangb3@mail.sysu.edu.cnPurpose: Quorum sensing (QS) system is crucial for biofilm formation, virulence and survival of Pseudomonas aeruginosa (P. aeruginosa). With the rise of antibiotic-resistant bacteria, QS inhibitors (QSIs) are seen as potential agents to mitigate infections. Plant-based natural products are rich sources of anti-QS compounds. Viola philippica Cav. (Violaceae) is traditionally used to treat inflammatory diseases, respiratory diseases and anti-microbials. However, its anti-QS effects against P. aeruginosa are poorly understood. We aimed to reveal the effects of scopoletin and scoparone from V. philippica Cav. extract (VPE) on QS-related virulence phenotypes and genes in P. aeruginosa PAO1.Materials and Methods: Compounds in VPE were identified using ultrahigh-performance liquid chromatography coupled with Q-exactive hybrid quadrupole-Orbitrap mass spectrometry (UHPLC-Q Exactive-Orbitrap MS). Virulence factors of PAO1, including pyocyanin, rhamnolipids, elastase, hemolysin, swarming and swimming motility, and biofilm formation, were evaluated. Real-time reverse transcription-polymerase chain reaction (RT-qPCR) was used to detect virulence-related genes. Bioassays for the QS inhibitory activity of VPE and its compounds were performed using Chromobacterium violaceum (C. violaceum) CV026.Results: Sub-minimum inhibitory concentrations (sub-MICs) of VPE inhibited QS-related virulence factors in PAO1, including pyocyanin, rhamnolipids, biofilms, and swarming motility. Scopoletin and scoparone, two coumarin derivatives identified in VPE using UHPLC-Q Exactive-Orbitrap MS, also showed anti-QS activity against PAO1. These compounds reduced pyocyanin, rhamnolipid, and hemolysin production, elastase activity, biofilm formation and swarming motility. Further RT-qPCR assays revealed that scopoletin and scoparone universally suppress QS-associated genes (lasI, rhlI and pqsA) in PAO1, primarily during the early and middle stages of growth.Conclusion: Scopoletin and scoparone, two previously uncharacterized coumarin derivatives from VPE, were identified as novel QSIs. They are responsible for VPE’s effect on weakening QS-controlled virulence of PAO1 by inhibiting QS-related genes. This study provides a laboratory basis for using scopoletin and scoparone as promising anti-virulence candidates for adjuvant therapy against P. aeruginosa infection.Keywords: PAO1, natural plant, Viola yedoensis makino, quorum sensing inhibitor, coumarin, Chromobacterium violaceum CV026